Co-fermentation experiments with agricultural main products and liquid pig manure - Sallai László (University of Szeged Faculty of Agriculture Hódmezővásárhely, 2016)
My research work proposes the study of the impact of the biogas production by the co-fermentation of agricultural products. The basic substance is the dangerous liquid pig manure of the concentrated stock of big pig farms. The energetic utilization of these materials means bigger income for the agricultural enterprises, savings in the replacement of the plant nutrition with the utilization of the bio-manure, increase in the performance of the plant production, making the dung harmless which means a big environmental load. Because of the profitability of bioenergy utilization depends on the local conditions, it is necessary to do experiments to try the available composition of organic wastes in the ratio of the production in advance. I measured the quantity of the methane and CO2 content of the biogas released from the substrate. The experiment simulated real biogas plant conditions, in mesophilic temperature, continuous biodegradation process. It can be considered, as a semi-industrial size.
Keywords: Mezőgazdaság-tudományok; Mezőgazdaság, erdészet, halászat